Who benefits from the procurement financed by Multilateral Development Banks? - Martínez-Galán, Enrique (2023)
We use a gravity model to inquire about the factors that influence the amount of public procurement awarded by developing countries with funding from Multilateral Development Banks (MDBs), based on 169 000 contracts. We reach four main conclusions. First, procurement disproportionately benefits firms of low- and middle-income countries and not those of MDBs' larger shareholders. Second, firms of upper-middle-income countries can compete successfully with those of developed countries. These two conclusions are in line with MDBs' development mandate. However, we also find that certain MDBs favour domestic firms and that having good diplomatic relations matters when awarding contracts.